2016
DOI: 10.1161/jaha.115.002889
|View full text |Cite
|
Sign up to set email alerts
|

Prasugrel, a Platelet P2Y 12 Receptor Antagonist, Improves Abnormal Gait in a Novel Murine Model of Thrombotic Hindlimb Ischemia

Abstract: BackgroundThe efficacy of P2Y12 inhibition for the prevention of cardiovascular events in patients with peripheral arterial disease (PAD) has been established. However, the therapeutic effects on ischemic limb complications are less clear. Accordingly, we aimed to develop a novel murine model of thrombotic hindlimb ischemia to reflect that found in patients with PAD exhibiting ischemic limb symptoms. We further investigated the effects of P2Y12 deficiency and P2Y12 inhibition by prasugrel in this model.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…These models of atherothrombosis in mice have been in use for several years. 30 31 32 33 34 35 All studies involving mice were reported in accordance with the ARRIVE guidelines. 37 38…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These models of atherothrombosis in mice have been in use for several years. 30 31 32 33 34 35 All studies involving mice were reported in accordance with the ARRIVE guidelines. 37 38…”
Section: Methodsmentioning
confidence: 99%
“…30 31 32 33 The FeCl 3 -induced thrombosis model is widely used as a standard method by thrombosis researchers. 34 35 In this article, we used this thrombosis model to study the antithrombotic effects of clopidogrel in STZ-treated apoE-deficient mice (diabetic apoE-deficient mice) compared with its antithrombotic effects in wild-type (WT) and nondiabetic apoE-deficient mice (apoE-deficient mice). Further, we determined the antiplatelet effects of clopidogrel in these three groups of mice.…”
Section: Introductionmentioning
confidence: 99%
“…Some mice were given intravascular heparin (300 U/kg) or eptifibatide (10 mg/kg) 15 minutes before initiation of pulmonary thrombosis (66,67). Prasugrel was suspended in a 5% solution of gum arabic (68) and administered once a day for 2 days and, additionally, approximately 4 hours before qFILM to each mouse by PO with a volume of 10 mL/kg. Physiological saline was intravascularly administered to mice as a vehicle in control experiments.…”
Section: R E S E a R C H A R T C L Ementioning
confidence: 99%